Perinatal programming factors of deviations of physical development of premature infants - K. V. Dashichev; N. V. Olendar; O. V. Kulibina; E. P. Sitnikova; T. L. Uspenskaya (LLC "Diagnostics and Vaccines", 2023)
The analysis of obstetric anamnesis and indicators of heart rate variability in the neonatal period in prematurely born children who had deviations of somatometric parameters from reference values at the age of 12 months was carried out. Excessive due to various reasons, the level of adrenomimetics supplied with maternal blood caused an increase in the intensity of metabolism in the fetal body and inhibition of the activity of sympathoadrenal systems. The insufficient provision of the fetal and newborn organism with energy and plastic materials that arose under these conditions initiated perinatal metabolic programming of deviations in the physical development of prematurely born infants.